Effect of Randomized PI Controller in Off Grid Network - Salimin, Suriana binti (International Journal of Integrated Engineering, 2019)
A stand- alone connection of photovoltaic (PV) system use power electronic components such as inverters and supply a non-linear load as users. This produce harmonics which adversely affect the power quality of the distribution network. A sinusoidal pulse width modulation (SPWM) of the voltage source inverter (VSI) is proposed to act as a switching pulse. The scheme to mitigate the harmonic problem and phase error in single-phase full bridge inverter is considered using low pass filter and current controller. The current control parameter using a conventional Proportional Integral (PI) is simulated. This is extended with the modification of control method where randomization control parameter technique is added to produce a more efficient current controller system by use random integral gain to the system. Result show the latter technique is better for reduction of harmonic rather than conventional PI controller technique